Static realization of reliable positional indication - Bushma, A.V.; Sukach, G.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The highly reliable position information model for optoelectronic display systems is offered. Logical operators that describe static formation of this model are obtained and analyzed. The main features of alphabets for two variants of this information model and information fields for their synthesis are investigated. Also offered are mathematical models for specific devices intended for highly reliable positional imaging information at the display consisting of elements with one common electrode. Analized and represented is their circuit solution.